The Importance Of Knowledge, Investment And Motivation For Gen-Z Interested In Investing - Winarsih Winarsih; Khoirul Fuad; Farah Aida Ahmad Nadzri (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2024)
This study aims to empirically prove investment knowledge, investment benefits and investment motivation on Gen-Z's investment interest in the capital market. This study is quantitative research. The population of this research is Gen-Z who are studying at universities in the city of Semarang. Primary data by distributing questionnaires to Gen-Z who are studying at universities in the city of Semarang, Indonesia using accidental sampling is the data source for this study. So there were 199 respondents obtained. Data processing using WarpPLS. The findings of this study show that investment knowledge, investment benefits, and investment motivation have an influence on the investment interest of Gen-Z who are studying at universities in the city of Semarang, Indonesia in the capital market. The implications of this study show that understanding and motivation is important for Gen-Z to invest in the capital market to gain additional income and investment experience.